THE IMPLEMENTATION OF DISCRETION ON CRIMINAL SETTLEMENT IN THE THEFT CASES - Muhammad Ikbal (IJCLS (Indonesian Journal of Criminal Law Studies), 2017)
On criminal law enforcement in Indonesia based on the principle of legality, especially in the case of theft criminal acts is necessary understanding of the purpose of punishment.Theft is a crime that has been formulated in the Indonesian Criminal Code, under Article 362. But punishment is not always done although the formulation of the offense is met because it sees in terms of subjective considerations of law enforcement. This research is normative research, so all data obtained in this research using secondary data. The results of this research are on the application of discretionary in settlement of criminal cases in the case of theft guided by the purpose of punishment and theories in the implementation of criminal law enforcement. So it is more to settling disputes out of court by using restorative justice approach.